A comprehensive study of the river plume in a microtidal setting. (30th September 2022) - Baldoni, Agnese; Perugini, Eleonora; Penna, Pierluigi; Parlagreco, Luca; Brocchini, Maurizio
Abstract: On the basis of observations and modelling of the plume generated by the Misa River (AN, Italy), we performed a comprehensive study, which integrated different sources of information (field data, numerical simulations, etc.), of the generation and transport mechanisms of river plumes flowing into microtidal environments. First, we analysed images simultaneously acquired by both two shore-based stations and satellite to determine plume fronts and extensions. Then, we correlated such information with the estuarine forcing to recognize the plume generation and transport mechanisms. Being real-life events influenced by a combination of factors, we run numerical simulations to separately study each force and its influence on the plume evolution. We also performed simulations of two real-life cases, to compare the modelled and observed results. We identified the river discharge and the wind as the main generation and transport mechanisms, respectively. Moreover, waves could stir, suspend, and drag plume sediments, even if results showed that a river discharge associated with a return period smaller than 1 year produced a plume denser than 5-year return period waves. The transport mechanisms were responsible for the alongshore extension of the plume. The tide, even if secondarily, affected the plume evolution, depending on its phase shift to the river discharge peak. Particle Tracking Velocimetry from videos acquired by a shore-based station provided the surface velocity field in the final river stretch. This and the contributions by wind and waves were correlated with the plume extension through a power law. Graphical abstract: Image 1 Highlights: Study of the local generation and transport mechanisms of a river plume using optical images, numerical modelling and PTV. The river discharge is the main plume generation mechanism, but also waves can resuspend riverbed sediments. Wind and waves affect the sediment dispersal to sea, defining the plume direction and the alongshore extension.